Dynamic interaction between Src and C-terminal Src kinase in integrin αIIbβ3-mediated signaling to the cytoskeleton - Vielreicher, Martin; Harms, Gregory; Butt, Elke; Walter, Ulrich; Obergfell, Achim (Journal of Biological Chemistry, 2007)
Integrin-bound Src tyrosine kinase mediates αIIbβ 3 outside-in signaling to the cytoskeleton required for platelet adhesion and thrombus formation. Src activation (signal initiation) by phosphorylation of Tyr-418 occurs at lamellipodia leading edges. However, little is known about Src inactivation mediated by C-terminal Src kinase (Csk) Tyr-529 phosphorylation. In an established platelet model cell line (A5-Chinese hamster ovary), we studied the inactivation of Src during αIIbβ 3-mediated adhesion to fibrinogen with live cell fluorescence resonance energy transfer (FRET) microscopy. Imaging revealed highly dynamic Src-Csk interactions at the leading edges of active lamellipodia. The Src-Csk interaction followed a highly dynamic pattern. Every 2-3 min, Src-Csk complexes moved inward in the cell, reorganized, and formed stable focal adhesions. These accumulations were primarily seen during retraction of lamellipodia, whereas no interaction was observed during protrusions. Western blot analysis during the run time of FRET signaling revealed an increase in Csk-mediated SrcTyr-529 phosphorylation with a parallel decline of tyrosine 418 phosphorylation. Mutation analysis provided additional insights into the role of Src. Although inactivation of Csk (CskK222R) had no effect on cell adhesion and spreading efficiency, cells with constitutively active expressed Src (SrcY529F) exhibited hardly any adhesion and no spreading. The few adherent cells showed weak focal adhesions that were disorganized and oversized. The data clearly demonstrate the important role of tight Src control by Csk for functional cell adhesion and spreading. The novel experimental FRET approach reported here for the inactivation of Src can be readily applied to other integrin and signaling pathways, including closely related Src family kinase members. © 2007 by The American Society for Biochemistry and Molecular Biology, Inc.
Created from Fastlane, Scopus look-up